2019
DOI: 10.26444/aaem/102762
|View full text |Cite
|
Sign up to set email alerts
|

Breast self-examination among nurses in Poland and their reparation in this regard

Abstract: Introduction and objective. Working at night and in shifts, as well as an unhealthy lifestyle, may increase the risk of breast cancer in nurses who therefore should frequently perform breast self-examination (BSE). The aim of the study was to investigate the performance of BSE among Polish nurses, its accuracy, sources of knowledge and skills, self-assessment of own competences and preparation to educate women about BSE. Materials and method. A descriptive, cross-sectional study was conducted in a group of fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…This is almost similar to the study conducted in the Philippines both standing and lying position but was lower than the study conducted in Poland. 30 , 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is almost similar to the study conducted in the Philippines both standing and lying position but was lower than the study conducted in Poland. 30 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…30 BSE practicing technique: In this study, correct BSE practicing techniques is the inspection of the breast in front of the mirror, palpation of the breasts with the pads of the fingers in a circular motion, or squeezing the tip of breasts for discharge. 30,31 Ever practiced BSE: practicing BSE at least once before. Frequency /regular BSE practice: the practice of BSE monthly.…”
Section: Positive Attitude Towards Bsementioning
confidence: 99%
“…In this study, only (16.4%) of nurses have taught BSE technique to their clients while (42.9%) polish nurses educate women [28]. The difference may be one of the reason to unsatisfactory result of accurate BSE practice in this study.…”
Section: Discussionmentioning
confidence: 74%
“…This study also identified that only (47.6 %) of nurses used all position of BSE while (58.9%) Poland nurses performed the examination both in the standing and lying position [28]. The discrepancy might be due to difference in the study area as Poland nurses may have had better experience and knowledge on BSE than Ethiopians.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation